2020
DOI: 10.2196/17559
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Telemonitoring on Patient Compliance With Self-Management Recommendations and Outcomes of the Innovative Telemonitoring Enhanced Care Program for Chronic Heart Failure: Randomized Controlled Trial

Abstract: Background Telemonitoring enables care providers to remotely support outpatients in self-managing chronic heart failure (CHF), but the objective assessment of patient compliance with self-management recommendations has seldom been studied. Objective This study aimed to evaluate patient compliance with self-management recommendations of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 31 publications
(42 reference statements)
3
77
0
2
Order By: Relevance
“…Telemedicine contributing to lifestyle improvement has been confirmed in other domains of medicine [ 50 - 56 ]. On the one hand, telemedicine provides patients and their caregivers with sustaining education on the necessity of lifestyle alterations [ 50 , 57 ]. On the other hand, timely feedback from clinicians enhances patients’ motivation to change their unhealthy lifestyles [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine contributing to lifestyle improvement has been confirmed in other domains of medicine [ 50 - 56 ]. On the one hand, telemedicine provides patients and their caregivers with sustaining education on the necessity of lifestyle alterations [ 50 , 57 ]. On the other hand, timely feedback from clinicians enhances patients’ motivation to change their unhealthy lifestyles [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 30 studies investigating non-invasive telemonitoring have been identified, including a total of 8892 patients [ 24 , 32 , 42 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. The study characteristics, as well as the reported outcomes on all-cause mortality, all-cause hospitalization, and HF-related hospitalization rates of the five largest studies, representing 52% (4606) of all patients, will be discussed in detail below [ 24 , 51 , 52 , 61 , 64 ].…”
Section: Non-invasive Telemonitoring Versus Usual Carementioning
confidence: 99%
“…The study characteristics, as well as the reported outcomes on all-cause mortality, all-cause hospitalization, and HF-related hospitalization rates of the five largest studies, representing 52% (4606) of all patients, will be discussed in detail below [ 24 , 51 , 52 , 61 , 64 ]. The study characteristics and outcomes of the other 25 studies will be summarized below [ 32 , 42 , 47 , 48 , 49 , 50 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 62 , 63 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Non-invasive Telemonitoring Versus Usual Carementioning
confidence: 99%
See 2 more Smart Citations